Nineteenth- and Twentieth-Century Photographs of the River Thames: The Collections of the Museum of London and the Port of London Authority. (November 2015) - Werner, Alex
Abstract : Historic photographs throw light on the Thames's past environment. This paper examines the Thames photographs that form part of two collections — those of the Museum of London and the Port of London Authority. These two collections developed in different ways, and have different strengths.